A LITERARY REVIEW OF SHILAJATU - Sharma Amit Kumar; Ritesh Ramnani; Mukesh Chaudhari; Manish kumar Saini; Sanjay Kumar (International Journal of Applied Ayurved Research, 2019)
Shilajatu is one of the Rasadravya (herbomineral drug) mentioned in the classical texts. Shilajatu is obtained from the mountain rocks in the form of exudate which oozes out in summer season. As per Charaka Samhita metals like gold and others are present in the rocks which receive the sun rays and secrete the exudates which is known as shilajatu. Ayurveda mentions it is wonderful medicine. Shodhita Shilajatu after bhavana can cure many diseases. In the present time Shilajatu is an important and irreplaceable place in classical text such as Ayurveda, Siddha and Unani medicine. Shilajatu is prescribed to treat Mutravaha shrotas vikar, Kamala, Swas roga, Kasa roga, Medoroga, Prameha and Madhumeha roga.etc.